Peningkatan Efektivitas Latihan Membaca untuk Anak Slow Learner di MIM Sraten - Intan Azaly; Najib Haidi Lutfillah; Nabila Azzahrah; Fannysha Septiani; Taqiyah Nurul’Azzah; Lorenza Jufri; Hani Pritananda Anisasiwi; Muhammad Amar Hanif; Mujiyati Mujiyati (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
This research aims to increase the focus on slow learner students, especially at MIM Sraten. The root of the problem found from observations with teachers is that slow learner students show behavior that is difficult to read. The problem found at MIM Sraten was that there were 19 students who were slow in reading. Method This service activity takes place at MIM Sraten from early August to early September 2024. Assistance is provided for 120 minutes at each session, with a focus on students who experience learning difficulties. The success of this program shows that a private approach that is personal and tailored to the needs of each child can be an effective model to be applied in other educational settings. This program also emphasizes the importance of ongoing training for teachers as well as collaboration between schools, parents and the community. It is hoped that this effort can have a positive and sustainable impact on literacy and intellectual development